(untitled) (International Seven Journal of Multidisciplinary, 2024)
Clean and renewable energy sources are strongly debated and are being seen as a great alternative to meet society’s energy demand, either for economic reasons or for reasons of lower carbon emissions, consequently there is a growing search for these energy sources. In this way, solar energy is gaining more and more space, especially in homes. With this, the objective of this study is an analysis of the implementation of a bifacial solar system in a residence, aiming at a better use of generation by installed space of the system. The advantage of the bifacial is the generation from the lower face, which can increase the electrical production in each panel by up to 25%.